Chitosan / corn starch slow-release antibacterial antioxidant multifunctional composite preservative film and preparation method thereof
By loading plant essential oils on porous corn starch and crosslinking with chitosan/corn starch, a composite plastic wrap with sustained release properties is formed, which solves the problem of insufficient antibacterial and antioxidant ability of the existing films and achieves efficient food preservation effect.
Patent Information
- Application Number
- CN202510138699.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The existing chitosan/corn starch films have insufficient antibacterial and antioxidant capacity, and their mechanical properties and sustained release properties are also poor, making it difficult to effectively extend the shelf life of food.
By loading plant essential oils into porous corn starch and crosslinking with chitosan/corn starch, a composite plastic wrap with sustained release properties is formed. The membrane enhances the mechanical properties and antibacterial and antioxidant properties of the membrane through the cross-linking of chitosan and corn starch.
It significantly improves the antibacterial and antioxidant properties of plastic wrap, extends the antibacterial and antioxidant effect time, improves the freshness effect of food, and meets the requirements of green and environmental protection.
Abstract
Description
[0001] The invention relates to the technical field of meat food preservation, and in particular to a chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite fresh-keeping film and a preparation method thereof. Background Art
[0002] With the increasing demand for food preservation, traditional food preservation methods mostly rely on chemical preservatives and artificial additives. Although these methods can extend the shelf life of food, they may cause potential harm to human health and the environment. Therefore, the research on natural preservative materials has received increasing attention. As a natural antibacterial and antioxidant ingredient, plant essential oils show good application prospects in food preservation. However, the high volatility and rapid release characteristics of plant essential oils limit their widespread application.
[0003] In the prior art, the invention patent CN115246945A provides a method for preparing a chitosan / starch / composite amino acid zinc edible film for the preservation of strawberries and other fruits and vegetables. The film is prepared by blending a chitosan solution with a corn starch solution and adding a composite amino acid zinc as a third component to prepare an edible film with antibacterial and antioxidant activity. However, the antibacterial spectrum of the composite amino acid zinc is narrow, and the inhibitory effect on certain specific microorganisms is limited. The invention patent CN118240285A provides an oxidized corn starch / polyethyleneimine / carboxymethyl chitosan composite film material, which is oxidized by sodium periodate, and the aldehyde group of the oxidized corn starch is chemically cross-linked with the amino group of polyethyleneimine, and then cross-linked with the amino group of carboxymethyl chitosan by genipin (genipin is the product of gardenia glycoside hydrolyzed by B-glucosidase, which is an excellent natural biological cross-linking agent, which can be cross-linked with proteins, collagen, gelatin and chitosan to make biomaterials) and carboxymethyl chitosan, to prepare a composite film material with good tensile properties and biodegradability. However, the antibacterial, antioxidant and sustained-release rate of the film have not been reported, so the preservation effect can be imagined to be average. Invention patent CN106883465A provides a preparation method of chitosan composite cling film, which prepares a cling film with excellent mechanical properties, antibacterial properties and barrier properties by compounding chitosan with modified nano-carbon crystals, but the sustained-release property is not good.
[0004] In order to solve the problems existing in the antibacterial property, antioxidant property and sustained release rate of the above-mentioned cling film, the present invention proposes to load plant essential oil on a carrier with sustained release performance to control the release rate of antibacterial antioxidant. Porous corn starch is adopted, because of its natural, degradable and non-toxic characteristics, it becomes an ideal sustained release carrier material. Chitosan is adopted as a biodegradable natural polymer material, has good biocompatibility and antibacterial property, and can be used for food packaging materials. Crosslinking corn starch with chitosan can not only improve the mechanical properties of the film, but also enhance its antibacterial and antioxidant functions and sustained release performance, so as to achieve the purpose of multifunctional fresh-keeping. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the defect of insufficient antibacterial and antioxidant capacity of the existing chitosan / corn starch film, while improving the mechanical properties and sustained release properties of the film, and to provide a chitosan / corn starch sustained release antibacterial and antioxidant multifunctional composite fresh-keeping film and a preparation method for food preservation.
[0006] The invention firstly adopts chitosan and corn starch as main raw materials, prepares chitosan acetic acid aqueous solution and gelatinized corn starch solution respectively, mixes the two solutions evenly, adds a crosslinking agent, and performs crosslinking reaction at a certain temperature to obtain a chitosan / corn starch crosslinking solution, then adsorbs an antibacterial antioxidant into a porous corn starch slow-release carrier; then evenly disperses the antibacterial antioxidant into the chitosan / starch crosslinking solution, adds a plasticizer, and obtains a film-forming solution; finally, vacuum degassing and drying film-forming methods are sequentially adopted to obtain a chitosan / corn starch slow-release antibacterial antioxidant multifunctional composite fresh-keeping film, thereby improving the mechanical properties, slow-release properties and antibacterial antioxidant properties of the composite film, and significantly improving the fresh-keeping effect of the multifunctional composite film.
[0007] A chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite fresh-keeping film, characterized in that it comprises the following components (by weight):
[0008] Corn starch: 10-20 parts;
[0009] Chitosan: 4-8 parts;
[0010] Porous corn starch: 2-3 parts;
[0011] Cross-linking agent: 10-12 parts;
[0012] Plasticizer: 6-8 parts;
[0013] Antibacterial antioxidant: 0.3-0.4 parts.
[0014] Preferably, the deacetylation degree of the chitosan is greater than 97%.
[0015] Preferably, the cross-linking agent is at least one of citric acid or malic acid.
[0016] Preferably, the antibacterial antioxidant is at least one of plant essential oils thymol or tea polyphenols.
[0017] Preferably, the plasticizer is glycerol, 1,3-butanediol or a combination thereof.
[0018] Preferably, the porous corn starch particles have a size of 1 to 10 μm and a specific surface area of 2 to 5 m 2 / g, pore volume is 0.8~1.5cm 3 / g.
[0019] Preferably, the method for preparing the multifunctional composite cling film comprises the following steps:
[0020] (1) Dissolve chitosan in an acetic acid aqueous solution with a mass fraction of 1 wt%, and perform ultrasonic degassing for 10 to 20 minutes to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0021] (2) Dispersing corn starch in water at a mass ratio of corn starch to water of 1:10-20, gelatinizing at 80-90° C. for 1-2 hours, and obtaining a gelatinized corn starch solution.
[0022] (3) The porous corn starch is dispersed in an ethanol-water system with a volume ratio of 1:3, and then an antibacterial antioxidant plant essential oil is added. The mixture is stirred at room temperature and adsorbed for 3 to 5 hours so that the active ingredients of the plant essential oil are fully loaded in the porous corn starch. The mixture is filtered and dried to obtain porous corn starch particles adsorbing the plant essential oil.
[0023] (4) The acetic acid aqueous solution in which chitosan is dissolved obtained in step (1) and the gelatinized corn starch solution obtained in step (2) are uniformly mixed, and then a cross-linking agent is added. The mixture is stirred and heated to 50 to 60° C., and the cross-linking reaction is carried out for 30 to 60 minutes. The mixture is then cooled to room temperature to obtain a chitosan / corn starch cross-linked solution.
[0024] (5) adding the porous corn starch particles adsorbing plant essential oil obtained in step (3) to the chitosan / corn starch cross-linked liquid obtained in step (4), and then adding a plasticizer, controlling the stirring rate to 150-400 rpm, and the stirring time to 10-15 min, to obtain a film-forming liquid.
[0025] (6) After the film-forming liquid obtained in step (5) is cast into a film in a rectangular tempered glass tray, it is first evacuated in a vacuum oven at room temperature for 2 to 3 hours to remove bubbles, thereby obtaining a vacuum degassing film.
[0026] (7) The tray containing the vacuum degassing film was placed in a forced air oven at 40 to 50° C. to dry the film for 12 to 15 h, and the cling film was gently torn off with tweezers to obtain a chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite cling film.
[0027] The advantages of the present invention are as follows:
[0028] (1) Natural and environmentally friendly: Corn starch and chitosan are used as the main raw materials, both of which are natural and biodegradable materials, non-toxic and harmless, and in line with the concept of green environmental protection.
[0029] (2) Excellent sustained-release performance: By loading plant essential oils through porous corn starch, the release rate of essential oils can be effectively controlled, thereby prolonging the antibacterial and antioxidant effect time.
[0030] (3) Strong antibacterial and antioxidant properties: After chitosan is cross-linked with corn starch, it synergizes with plant essential oils to significantly enhance the antibacterial and antioxidant capabilities of the film.
[0031] (4) Enhanced mechanical properties: After chitosan and corn starch are cross-linked, the tensile strength increases.
[0032] (5) Simple preparation process: The preparation method is easy to operate, the raw materials are easily available, and it is suitable for large-scale production.
[0033] The present invention is further described in detail below through specific examples. In the following examples, the various index test methods of the chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite cling film are all commonly used methods for cling film performance testing in the industry, and are as follows:
[0034] (1) Mechanical properties: Refer to GB / T 1040 standard to test the tensile strength and elongation at break of the film.
[0035] (2) Antibacterial property: The antibacterial ability of the cling film described in this patent application was tested using a coating method.
[0036] (3) Antioxidant activity: The antioxidant activity of the membranes was determined by the DPPH free radical scavenging test.
[0037] (4) Sustained release performance: 3 g of the film was immersed in 250 mL of 95% ethanol solution at room temperature, and 1 mL of the solution was taken at different time intervals to test the amount of thymol or tea polyphenols therein by ultraviolet spectrophotometry. The time and release rate when the release of thymol or tea polyphenols from the film reached equilibrium, i.e., when the amount of thymol or tea polyphenols in the solution did not change, were determined. DETAILED DESCRIPTION
[0038] Example 1
[0039] (1) 8 parts of chitosan were dissolved in 200 mL of 1% acetic acid aqueous solution, and the bubbles were removed by ultrasonication for 10 min to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0040] (2) Disperse 10 parts of corn starch in 190 mL of water, stir under reflux, and heat in a 90° C. water bath for 2 h to obtain a gelatinized corn starch solution.
[0041] (3) 2 parts of porous corn starch were dispersed in 40 mL of a mixed solution of ethanol and water with a volume ratio of 1:3, and 0.3 parts of thymol were added. The mixture was stirred and adsorbed at room temperature for 3 h so that the thymol active ingredient was fully loaded in the porous corn starch. The mixture was filtered and dried to obtain porous corn starch particles adsorbing thymol.
[0042] (4) The chitosan acetic acid aqueous solution obtained in step (1) and the gelatinized corn starch solution obtained in step (2) were uniformly mixed, 12 parts of anhydrous citric acid as a cross-linking agent were added, the mixture was stirred and heated to 60° C., the cross-linking reaction was carried out for 30 minutes, and then the mixture was cooled to room temperature to obtain a chitosan / corn starch cross-linked solution.
[0043] (5) The porous corn starch adsorbed with thymol obtained in step (3) is added to the chitosan / corn starch cross-linked liquid obtained in step (4), and then 6 parts of plasticizer glycerol are added, the stirring rate is controlled to 150 rpm, and the stirring time is 10 min to obtain a film-forming liquid.
[0044] (6) The solution obtained in step (5) was poured into a rectangular tempered glass tray of 25.5×45 cm, and placed in a vacuum oven at room temperature for 3 h to remove bubbles and obtain a vacuum degassing film.
[0045] (7) The tray containing the vacuum degassing film was placed in a 40°C forced air oven to dry for 14 h, and the cling film was gently torn off with tweezers to obtain a chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite cling film.
[0046] Example 2
[0047] (1) Dissolve 4 parts of chitosan in 200 mL of 1% acetic acid aqueous solution, and remove bubbles by ultrasonication for 10 min to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0048] (2) Disperse 20 parts of corn starch in 180 mL of water, stir under reflux, and heat in a 90° C. water bath for 2 h to obtain a gelatinized corn starch solution.
[0049] (3) Disperse 3 parts of porous corn starch in 40 mL of a 1:3 ethanol-water mixed solution, add 0.36 parts of antibacterial antioxidant tea polyphenols, and stir and adsorb at room temperature for 5 h to allow the active ingredients of tea polyphenols to be fully loaded in the porous corn starch. Filter and dry to obtain porous corn starch particles adsorbing tea polyphenols.
[0050] (4) The chitosan acetic acid aqueous solution obtained in step (1) and the gelatinized corn starch solution obtained in step (2) were uniformly mixed, 12 parts of anhydrous citric acid as a cross-linking agent were added, the mixture was stirred and heated to 55° C., the cross-linking reaction was carried out for 45 minutes, and the mixture was cooled to room temperature to obtain a chitosan / corn starch cross-linked solution.
[0051] (5) The porous corn starch adsorbing tea polyphenols obtained in step (3) is added to the chitosan / corn starch cross-linked liquid obtained in step (4), and then 8 parts of plasticizer glycerol are added. The stirring rate is controlled to 450 rpm and the stirring time is 15 min to obtain a film-forming liquid.
[0052] (6) Pour the solution obtained in step (5) into a 25.5×45 cm rectangular tempered glass tray and place it in a vacuum oven at room temperature for 2.5 h to remove bubbles and obtain a vacuum degassing film
[0053] (7) The tray containing the vacuum degassing film was placed in a 40°C forced air oven to dry for 15 h, and the cling film was gently torn off with tweezers to obtain a chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite cling film.
[0054] Example 3
[0055] (1) Dissolve 6 parts of chitosan in 200 mL of 1% acetic acid aqueous solution, and remove bubbles by ultrasonication for 15 min to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0056] (2) Disperse 15 parts of corn starch in 185 parts of water, stir under reflux, and heat in a 90° C. water bath for 2 h to obtain a gelatinized corn starch solution.
[0057] (3) 2.5 parts of porous corn starch were dispersed in 40 mL of an ethanol-water mixed solution with a volume ratio of 1:3, and 0.36 parts of the antibacterial antioxidant thymol were added. The mixture was stirred and adsorbed at room temperature for 4 hours to allow the thymol active ingredient to be fully loaded in the porous corn starch. The mixture was filtered and dried to obtain porous corn starch particles adsorbing thymol.
[0058] (4) The chitosan acetic acid aqueous solution obtained in step (1) and the gelatinized corn starch solution obtained in step (2) were uniformly mixed, 10 parts of malic acid as a cross-linking agent were added, the mixture was stirred and heated to 50° C., the cross-linking reaction was carried out for 60 minutes, and then the mixture was cooled to room temperature to obtain a chitosan / corn starch cross-linked solution.
[0059] (5) The porous corn starch adsorbing tea polyphenols obtained in step (3) is added to the chitosan / corn starch cross-linked liquid obtained in step (4), and then 6 parts of plasticizer 1,3-butanediol are added. The stirring rate is controlled to 300 rpm and the stirring time is 10 min to obtain a film-forming liquid.
[0060] (6) The solution obtained in step (5) was poured into a rectangular tempered glass tray of 25.5×45 cm, and placed in a vacuum oven at room temperature for 3 h to remove bubbles and obtain a vacuum degassing film.
[0061] (7) The tray containing the vacuum degassing film was placed in a 50°C forced air oven to dry for 12 h, and the cling film was gently torn off with tweezers to obtain a chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite cling film.
[0062] Comparative Example 1
[0063] Comparative Example 1 is that in Example 1, no anhydrous citric acid cross-linking agent is added, and no porous corn starch particles adsorbed with thymol are added. Other contents are the same as in Example 1, and the specific steps are as follows:
[0064] (1) Dissolve 7 parts of chitosan in 200 mL of 1% acetic acid aqueous solution, and remove bubbles by ultrasonication for 10 min to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0065] (2) Disperse 10 parts of corn starch in 190 mL of water, stir under reflux, and heat in a 90° C. water bath for 2 h to obtain a gelatinized corn starch solution.
[0066] (3) The chitosan acetic acid aqueous solution obtained in step (1) and the gelatinized corn starch solution obtained in step (2) are uniformly mixed, and then 6 parts of plasticizer glycerol are added, and the stirring rate is controlled to be 150 rpm and the stirring time is 10 min to obtain a chitosan / corn starch composite solution.
[0067] (4) The composite liquid obtained in step (3) was poured into a 25.5×45 cm tempered glass tray, placed in a vacuum oven and evacuated for 3 h to remove bubbles, thereby obtaining a vacuum degassing film.
[0068] (5) The tray containing the vacuum degassing film was placed in a 40° C. forced air oven to dry for 15 h, and the cling film was gently torn off with tweezers to obtain the cling film of Comparative Example 1.
[0069] Comparative Example 2
[0070] Comparative Example 2 is the same as Example 1 except that the porous corn starch particles adsorbing thymol are not added thereto. The specific steps are as follows:
[0071] (1) 8 parts of chitosan were dissolved in 200 mL of 1% acetic acid aqueous solution, and the bubbles were removed by ultrasonication for 10 min to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0072] (2) Disperse 10 parts of corn starch in 190 mL of water, stir under reflux, and heat in a 90° C. water bath for 2 h to obtain a gelatinized corn starch solution.
[0073] (3) The chitosan acetic acid aqueous solution obtained in step (1) and the gelatinized corn starch solution obtained in step (2) were uniformly mixed, 12 parts of anhydrous citric acid as a cross-linking agent were added, the mixture was stirred and heated to 60° C., the cross-linking reaction was carried out for 30 minutes, and the mixture was cooled to room temperature to obtain a chitosan / corn starch cross-linked solution.
[0074] (4) 6 parts of plasticizer glycerol were then added to the chitosan / corn starch cross-linked solution obtained in step (3), and the stirring rate was controlled to 150 rpm and the stirring time was 10 min to obtain a film-forming solution.
[0075] (5) The film-forming liquid obtained in step (4) was poured into a 25.5×45 cm tempered glass tray, placed in a vacuum oven and evacuated for 3 h to remove bubbles, thereby obtaining a vacuum degassing film.
[0076] (6) The tray containing the vacuum degassing film was placed in a 40° C. forced air oven to dry for 15 h, and the cling film was gently torn off with tweezers to obtain the cling film of Comparative Example 2.
[0077] Comparative Example 3
[0078] Comparative Example 3 is that the porous corn starch particles adsorbing thymol are not added in Example 1, but thymol is directly added. The other contents are the same as those in Example 1, and the specific steps are as follows:
[0079] (1) 8 parts of chitosan were dissolved in 200 mL of 1% acetic acid aqueous solution, and the bubbles were removed by ultrasonication for 10 min to obtain a clear and transparent chitosan acetic acid aqueous solution.
[0080] (2) Disperse 10 parts of corn starch in 190 mL of water, stir under reflux, and heat in a 90° C. water bath for 2 h to obtain a gelatinized corn starch solution.
[0081] (3) Dissolve 0.3 parts of thymol in 40 mL of an ethanol-water mixed solution with a volume ratio of 1:3 to obtain an ethanol-water solution in which thymol is dissolved.
[0082] (4) The chitosan acetic acid aqueous solution obtained in step (1) and the gelatinized corn starch solution obtained in step (2) were uniformly mixed, 12 parts of anhydrous citric acid as a cross-linking agent were added, the mixture was stirred and heated to 60° C., the cross-linking reaction was carried out for 30 minutes, and then the mixture was cooled to room temperature to obtain a chitosan / corn starch cross-linked solution.
[0083] (5) adding the ethanol-water solution in which thymol is dissolved obtained in step (3) to the chitosan / corn starch cross-linked liquid obtained in step (4), and then adding 6 parts of plasticizer glycerol, controlling the stirring rate to 150 rpm and the stirring time to 10 min, to obtain a film-forming liquid.
[0084] (6) The solution obtained in step (5) was poured into a 25.5×45 cm tempered glass tray, placed in a vacuum oven and evacuated for 3 h to remove bubbles, thereby obtaining a vacuum degassing film.
[0085] (7) The tray containing the vacuum degassing film was placed in a 40° C. forced air oven to dry for 15 h, and the cling film was gently torn off with tweezers to obtain the cling film of Comparative Example 3.
[0086] Tensile properties and elongation at break tests
[0087] The chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite fresh-keeping film provided by the present invention shows excellent performance in tensile strength and elongation at break. The tensile strengths of Example 1, Example 2 and Example 3 reached 13.11MPa, 11.21MPa and 13.17MPa respectively, and the elongation at break exceeded 218%, indicating that the cross-linked structure of chitosan and corn starch and the synergistic effect of plasticizers (glycerol, 1,3-butanediol) significantly improved the mechanical properties and flexibility of the film. The addition of porous corn and cross-linking agents (anhydrous citric acid, malic acid) further enhanced the tensile strength of the film, while the loading of plant essential oils (such as thymol) had little effect on the mechanical properties, but the strength may be slightly improved by enhancing the intermolecular forces. Comparative Example 1 lacks a cross-linking agent, and the tensile strength is significantly lower, reaching only 5.11MPa, and the mechanical properties are the worst, while Comparative Examples 2 and Comparative Examples 3 both have cross-linking agents, and their mechanical properties are comparable to those of Examples 1, 2 and 3, highlighting the key role of cross-linking agents in film performance. In general, the present invention successfully develops a fresh-keeping film with high tensile strength and good flexibility by optimizing the formula and preparation process, which is suitable for the field of food preservation.
[0088] Table 1 Tensile properties and elongation at break of different examples project Added / unadded agents Tensile strength(MPa) Elongation at break (%) Example 1 Cross-linking agent, sustained-release agent, antibacterial antioxidant 13.11 218.31 Example 2 Cross-linking agent, sustained-release agent, antibacterial antioxidant 11.21 223.12 Example 3 Cross-linking agent, sustained-release agent, antibacterial antioxidant 13.17 220.12 Comparative Example 1 No cross-linking agent, no sustained-release agent, no antibacterial antioxidant 5.11 180.12 Comparative Example 2 Cross-linking agent, no sustained-release agent, no antibacterial antioxidant 12.31 220.35 Comparative Example 3 Cross-linking agent, no sustained-release agent, antibacterial antioxidant 13.34 222.34
[0089] Antibacterial performance test
[0090] The present invention significantly improves the antibacterial properties of the fresh-keeping film by loading plant essential oils in porous corn starch and mixing with the film-forming liquid after chitosan / corn starch cross-linking. Table 2 shows the size of the antibacterial zone of the fresh-keeping film of different embodiments and different comparative examples. Example 1, Example 2, and Example 3 respectively use porous corn starch to load thymol, tea polyphenols, and thymol, and the antibacterial zones of the fresh-keeping films reach 25.5mm, 20.7mm, and 23.4mm, respectively. The antibacterial effect of porous corn starch loaded thymol is better than that of porous corn starch loaded tea polyphenols. Comparative Example 3 directly adds thymol, and the antibacterial zone of the fresh-keeping film is 23.2mm, indicating that the addition of plant essential oils significantly improves its antibacterial properties, and its effect is significantly better than that of Comparative Example 1 and Comparative Example 2 without adding plant essential oils. Mainly due to the synergistic effect of thymol and chitosan, the antibacterial action time is extended, and the antibacterial ability of the film is further enhanced. In general, the present invention successfully develops a fresh-keeping film with excellent antibacterial properties, which is suitable for the field of food preservation.
[0091] Table 2 Antibacterial effect of plastic wrap at different time points project Chemicals added / not added Inhibition zone size (mm) Example 1 Cross-linking agent, sustained-release agent, antibacterial antioxidant 25.5 Example 2 Cross-linking agent, sustained-release agent, antibacterial antioxidant 20.7 Example 3 Cross-linking agent, sustained-release agent, antibacterial antioxidant 23.4 Comparative Example 1 No cross-linking agent, no sustained-release agent, no antibacterial antioxidant 13.7 Comparative Example 2 Cross-linking agent, no sustained-release agent, no antibacterial antioxidant 14.1 Comparative Example 3 Cross-linking agent, no sustained-release agent, antibacterial antioxidant 23.2
[0092] Antioxidant performance test
[0093] The present invention significantly improves the antioxidant properties of the fresh-keeping film by loading plant essential oils (such as thymol and tea polyphenols) into porous corn and cross-linking with chitosan / corn starch, as shown in Table 3. The antioxidant activities of Example 1, Example 2, Example 3 and Comparative Example 3 shown in Table 3 are all over 75%, and their antioxidant effects are significantly better than Comparative Example 1 and Comparative Example 2 without adding plant essential oils, and are equivalent to the antioxidant effect of Comparative Example 3 directly adding plant essential oils. It can be seen that thymol or tea polyphenols plant essential oils can significantly enhance the antioxidant effect of the film. In general, the present invention successfully develops a fresh-keeping film with excellent antioxidant properties, which is suitable for the field of food preservation.
[0094] Table 3 Antioxidant properties of different examples project Chemicals added / not added Antioxidant activity (%) Example 1 Cross-linking agent, sustained-release agent, antibacterial antioxidant 76.34 Example 2 Cross-linking agent, sustained-release agent, antibacterial antioxidant 75.48 Example 3 Cross-linking agent, sustained-release agent, antibacterial antioxidant 77.12 Comparative Example 1 No cross-linking agent, no sustained-release agent, no antibacterial antioxidant 10.13 Comparative Example 2 Cross-linking agent, no sustained-release agent, no antibacterial antioxidant 8.59 Comparative Example 3 Cross-linking agent, no sustained-release agent, antibacterial antioxidant 74.81
[0095] Plant essential oil release performance test
[0096] Table 4 compares the release rates of the composite films of the embodiments and the comparative examples in 95% ethanol food simulation liquid. The release times of thymol, tea polyphenols and thymol in the composite films of Examples 1, 2 and 3 tend to equilibrium at 3840, 3910 and 3720 min, respectively, and the release rates are 75.45, 72.02 and 77.64%, respectively. In Comparative Example 3, porous corn was not used to load thymol, but thymol was directly used, and the release rate of its composite film reached release equilibrium at 3360 min, with a release rate of 80.34%. Compared with the multifunctional composite film using porous corn to load thymol, the time for its release to reach equilibrium is shorter, the release rate is slightly higher, and the purpose of sustained release is not achieved. It can be seen that porous corn starch plays a "protective" role for plant essential oils, effectively prolongs the release time of plant essential oils, and realizes the sustained release of plant essential oils. Comparative Examples 1 and 2 do not use thymol, so there is no release equilibrium time and release rate. The porous corn is used as a slow-release carrier to effectively control the release rate of the plant essential oil. In general, the invention successfully develops a fresh-keeping film with excellent slow-release performance, which is suitable for the field of food preservation.
[0097] Table 4 Sustained release of plant essential oils (thymol and tea polyphenols) project Plant essential oil status Time to reach release equilibrium, min Release rate (%) Example 1 Porous corn starch adsorbs thymol 3840 75.45 Example 2 Porous corn starch absorbs tea polyphenols 3910 72.02 Example 3 Porous corn starch adsorbs thymol 3720 77.64 Comparative Example 1 No essential oils none none Comparative Example 2 No essential oils none none Comparative Example 3 Add thymol directly 3360 80.34
[0098] In summary, the present invention successfully develops a multifunctional composite fresh-keeping film with excellent sustained-release performance, mechanical properties, antioxidant properties and antibacterial properties, which is suitable for the field of food preservation.
Claims
1. A chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite fresh-keeping film, characterized in that: It includes the following components (by weight): Corn starch: 10-20 parts; Chitosan: 4-8 parts; Porous corn starch: 2-3 parts; Cross-linking agent: 10-12 parts; Plasticizer: 6-8 parts; Antibacterial antioxidant: 0.3-0.4 parts.
2. The chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite fresh-keeping film according to claim 1, characterized in that: The deacetylation degree of the chitosan is greater than 97%.
3. The chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite fresh-keeping film according to claim 1, characterized in that: The cross-linking agent is at least one of citric acid and malic acid.
4. The chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite fresh-keeping film according to claim 1, characterized in that: The antibacterial antioxidant is at least one of plant essential oil thymol or tea polyphenols.
5. The chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite fresh-keeping film according to claim 1, characterized in that: The plasticizer is glycerol, 1,3-butanediol or a combination thereof.
6. The chitosan / corn starch sustained-release antibacterial and antioxidant multifunctional composite fresh-keeping film according to claim 1, characterized in that: The porous corn starch particles have a size of 1 to 10 μm and a specific surface area of 2 to 5 m 2 / g, pore volume is 0.8~1.5cm 3 / g.
7. A chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite fresh-keeping film according to claim 1, characterized in that: The preparation method of the cling film comprises the following steps: (1) dissolving chitosan in an aqueous solution of acetic acid having a mass fraction of 1%, and performing ultrasonic degassing for 10 to 20 minutes to obtain a clear and transparent aqueous solution of chitosan in acetic acid; (2) dispersing corn starch in water at a mass ratio of corn starch to water of 1:10-20, and gelatinizing at 80-90° C. for 1-2 hours to obtain a gelatinized corn starch liquid; (3) dispersing the porous corn starch in an ethanol-water system with a volume ratio of 1:3, adding an antibacterial antioxidant plant essential oil, stirring and adsorbing for 3 to 5 hours at room temperature, so that the active ingredients of the plant essential oil are fully loaded in the porous corn starch, filtering and drying, and obtaining porous corn starch particles adsorbing the plant essential oil; (4) uniformly mixing the acetic acid aqueous solution in which chitosan is dissolved obtained in step (1) and the gelatinized corn starch solution obtained in step (2), adding a crosslinking agent, stirring, heating to 50-60° C., crosslinking reaction for 30-60 min, and cooling to room temperature to obtain a chitosan / corn starch crosslinked solution; (5) adding the porous corn starch particles adsorbing the plant essential oil obtained in step (3) to the chitosan / corn starch cross-linked liquid obtained in step (4), and then adding a plasticizer, controlling the stirring rate to 150 to 400 rpm, and the stirring time to 10 to 15 minutes, to obtain a film-forming liquid; (6) casting the solution obtained in step (5) into a film in a rectangular tempered glass tray, and then evacuating the film in a vacuum oven at room temperature for 2 to 3 hours to remove bubbles, thereby obtaining a vacuum degassing film; (7) The tray containing the vacuum degassing film was placed in a forced air oven at 40 to 50° C. to dry the film for 12 to 15 h, and the cling film was gently torn off with tweezers to obtain a chitosan / corn starch slow-release antibacterial and antioxidant multifunctional composite cling film.
Citation Information
Patent Citations
Preparation method of chitosan composite preservative film
CN106883465A
Oxidized corn starch / polyethyleneimine / carboxymethyl chitosan composite membrane material
CN118240285A
Preparation method of edible film with antibacterial and antioxidant functions
CN103159970A
Edible antibacterial cling film, and preparation method and application thereof
CN108395705A
Preparation method and application of antibacterial active food packaging film
CN110078958A
Cited By
Food antioxidant preservative film and preparation method thereof
CN120944230A